2015
DOI: 10.1186/s12876-015-0258-6
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic acute pancreatitis with pancreatic pseudocyst in a patient with abdominal aortic aneurysm and generalized atheromatosis – case report

Abstract: BackgroundIschemic pancreatitis is a rare medical entity. The pancreatic tissue is susceptible to ischemia with the possibility of developing acute pancreatitis. The abdominal aortic aneurysm can be one possible cause of pancreatic hypoperfusion.Case presentationWe report the case of a 68-year-old man, Caucasian, with a history of a cluster of severe cardiovascular conditions, who presented epigastric pain of variable intensity for about 2 weeks. The pain occurred after intense physical effort, and was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…It has previously been hypothesised that AAAs, through occlusion of aortic branches may lead to pancreatic hypoperfusion and consequently to ischaemia and subsequent pancreatitis. Cocota et al reported a case of acute pancreatitis in association with an aneurysm and hypothesised that a combination of a thrombosed aneurysm, generalised atheromatous disease and intense physical activity prior to presentation lead to the development of acute pancreatitis 11. This is a plausible explanation in our case given the large aneurysm and extensive atherosclerosis present.…”
Section: Discussionmentioning
confidence: 57%
“…It has previously been hypothesised that AAAs, through occlusion of aortic branches may lead to pancreatic hypoperfusion and consequently to ischaemia and subsequent pancreatitis. Cocota et al reported a case of acute pancreatitis in association with an aneurysm and hypothesised that a combination of a thrombosed aneurysm, generalised atheromatous disease and intense physical activity prior to presentation lead to the development of acute pancreatitis 11. This is a plausible explanation in our case given the large aneurysm and extensive atherosclerosis present.…”
Section: Discussionmentioning
confidence: 57%
“…Patients developing IP have been reported in cases with clinically significant AP and have shown convincingly that this is one of the known causes of AP 5–17. The only case series previously describing IP consisted of 11 patients from a tertiary referral center in Germany 5.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic pancreatitis (IP) is a poorly defined clinical condition and there is no consensus on diagnostic criteria. Most of the literature on IP is based on case reports with a large variety of causes of IP 3–17. The largest study published to date is a study of patients with IP from a surgical department in Germany with 11 patients with IP of different underlying conditions 5.…”
mentioning
confidence: 99%
“…Hypertension [17], cardiovascular disease [17,18], and diabetes [19,20] have been independently associated with the incidence of AP. Indeed, a higher number of the comorbid disease has been shown to associate with poorer outcomes in AP, including the length of hospitalisation and mortality [21].…”
Section: Discussionmentioning
confidence: 99%